14-3-3ζ allows for adipogenesis by modulating chromatin accessibility during the early stages of adipocyte differentiation - Sabri A. Rial; Zhipeng You; Alexis Vivoli; Fédéric Paré; Daphné Sean; Amal AlKhoury; Geneviève Lavoie; Mete Civelek; Aida Martinez-Sanchez; Philippe P. Roux; Thomas M. Durcan; Gareth E. Lim (Molecular Metabolism)
Objective: We previously established the scaffold protein 14-3-3ζ as a critical regulator of adipogenesis and adiposity, but whether 14-3-3ζ exerted its regulatory functions in mature adipocytes or in adipose progenitor cells (APCs) remained unclear. Methods: To decipher which cell type accounted for 14-3-3ζ-regulated adiposity, adipocyte- (Adipoq14-3-3ζKO) and APC-specific (Pdgfra14-3-3ζKO) 14-3-3ζ knockout mice were generated. To further understand how 14-3-3ζ regulates adipogenesis, Tandem Affinity Purification (TAP)-tagged 14-3-3ζ-expressing 3T3-L1 preadipocytes (TAP-3T3-L1) were generated with CRISPR-Cas9, and affinity proteomics was used to examine how the nuclear 14-3-3ζ interactome changes during the initial stages of adipogenesis. ATAC-seq was used to determine how 14-3-3ζ depletion modulates chromatin accessibility during differentiation. Results: We show a pivotal role for 14-3-3ζ in APC differentiation, whereby male and female Pdgfra14-3-3ζKO mice displayed impaired or potentiated weight gain, respectively, as well as fat mass. Proteomics revealed that regulators of chromatin remodeling, like DNA methyltransferase 1 (DNMT1) and histone deacetylase 1 (HDAC1), were significantly enriched in the nuclear 14-3-3ζ interactome and their activities were impacted upon 14-3-3ζ depletion. Enhancing DNMT activity with S-Adenosyl methionine rescued the differentiation of 14-3-3ζ-depleted 3T3-L1 cells. ATAC-seq revealed that 14-3-3ζ depletion impacted the accessibility of up to 1,244 chromatin regions corresponding in part to adipogenic genes, promoters, and enhancers during the initial stages of adipogenesis. Finally, 14-3-3ζ-regulated chromatin accessibility correlated with the expression of key adipogenic genes. Conclusion: Our study establishes 14-3-3ζ as a crucial epigenetic regulator of adipogenesis and highlights the usefulness of deciphering the nuclear 14-3-3ζ interactome to identify novel pro-adipogenic factors and pathways.